Rancang Bangun Sistem Informasi Petty Cash Dengan Pendekatan Modifikasi Extreme Programming : Studi Kasus PT XYZ - Mulyana, Ade; Hermawan, Yanto; Listari, Sinta (Jurnal Aplikasi Bisnis Kesatuan, 2024)
The Petty Cash Information System plays an important role in managing the daily operational funds of the company. PT. XYZ is a company engaged in the banking sector. Given the importance of efficiency and accuracy in managing Petty Cash for the company, this research aims to design and build a web-based Petty Cash information system that can assist PT. XYZ in managing and monitoring their small cash funds. The methodology used in this research is Agile Extreme Programming method, which includes system requirements analysis, system design, and web-based application development. The system requirements analysis involves identifying the needs and requirements necessary for managing Petty Cash. Based on the results of the requirements analysis, a system design is created that includes database design, user interface, and system workflow. It is expected that by implementing this system, a prototype for the Petty Cash information system will be generated, which can potentially be implemented by PT. XYZ to enhance efficiency, accuracy, and control over Petty Cash management in the company.   Keywords: Design and Development, Petty Cash, Web -Based, Agile, Extreme Programming